Leper knights : the order of St. Lazarus of Jerusalem in England, c.1150-1544 - Marcombe, David (Studies in the history of medieval religion ;, 2003)
One of the most unusual contributions to the crusading era was the idea of the leper knight - a response to the scourge of leprosy and the shortage of fighting men which beset the Latin kingdom in the twelfth century. The Order of St Lazarus, which saw the idea become a reality, founded establishments across Western Europe to provide essential support for its hospitaller and military vocations. This book explores the important contribution of the English branch of the order, which by 1300 managed a considerable estate from its chief preceptory at Burton Lazars in Leicestershire.